Portuguese irregular verbs - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Professor Dr. von Igelfeld entertainment novel., 2005)
Professor Dr von Igelfeld learns to play tennis, and forces a college chum to enter into a duel that results in a nipped nose. He also takes a field trip to Ireland where he becomes acquainted with the rich world of archaic Irishisms, and he develops an aching infatuation with a Dentist fatale. Along the way, he takes two ill-fated Italian sojourns, the first merely uncomfortable, the second definitely dangerous.